Disparitas Pidana Dalam Kasus Tindak Pidana Pencucian Uang Hasil Tindak Pidana Narkotika - Gultom, Santo Barri; Efendi, Erdianto; Indra, Mexsasai (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
Criminal sanctions aim to give preferential suffering to the offender so that he felt as aresult of his actions. In addition aimed at imposing suffering against the perpetrators,criminal sanctions also constitute a statement of disapproval against offenders act. In the caseof money laundering narcotics proceeds of crime, criminal sanctions is necessary as adeterrent effect imposed by the judge to the perpetrators of money laundering narcoticsproceeds of crime. But often found differences in criminal sanctions against the judgeimposed the same case, or better known as the Criminal Disparities resulting in theemergence of injustice. Criminal is a criminal disparity unequal application of the samecriminal acts without apparent justification. This study examines the problems of (1) How isthe construction of thinking judges in decisions in the case of money laundering narcoticsproceeds of crime in the case Number: 593 / PID / SUS / 2012 / PN.PBR and case Number:258 / PID / SUS / 2014 /PN.PBR? (2) Are the causes of dispartitas verdict against moneylaundering narcotics proceeds of crime. The goal in this study to determine construction thinkjudges in imposing criminal verdict in the case Number: 593 / PID / SUS / 2012 / PN.PBRand case Number: 258 / PID / SUS / 2014 / PN.PBR? and also to determine the factors thatcause disparities verdict against money laundering narcotics proceeds of crime. From theresults of this study concluded (1) that in case Number: 593 / PID / SUS / 2012 / PN.PBRdefendant is proven guilty of money laundering as stipulated in Law No. 8 of 2010 withsentenced to imprisonment for 3 (three) years and a fine Rp.800.000.000, - (eight hundredmillion dollars) and in case Number: 258 / PID / SUS / 2014 / PN.PBR defendant was legallycommit money laundering continues, the defendant shall be sentenced to prison for 1 ( one)year 2 (two) months and a fine of Rp. 100.000.000, - (one hundred million rupiah). (2) Thecause of the disparity verdict against the same criminal act caused by the law itself factors,factors resources law enforcement officials, a factor of self-judge itself (both internal andexternal) and also the factors of the situation inside the defendant. This study suggested thatthe government mengandemen Law on Money Laundering which so no criminalclassification is based on the type of predicate offenses, the amount of money obtained fromthe predicate offense, and specifically for money laundering predicate crime that his narcoticcrime to establish regulations for the amount and type of drugs so that the judge in makingthe interpretation of the statute can be limited.Keywords: Disparity, Criminal, Money Laundering.